ANALISIS AKUNTABILITAS PENGELOLAAN ZAKAT PADA BAITUL MAL DAN RUMAH ZAKAT DI KOTA BANDA ACEH - Mutia, Evi; Fadhil, Muhammad; Rahmawaty, Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
Baitul Mal Banda Aceh and Rumah Zakat Aceh are organizations that are trusted by muzakki in distributed zakat to mustahiq in Banda Aceh city. The purpose of this study is to see how the accountability and management of zakat in Baitul Mal Banda Aceh and Rumah zakat Aceh in order to increase public trust in management of zakat institutions. The method used is descriptive analysis method with a qualitative research approach. The research data collection is done through field research with data collection techniques through interviews and documentation. The results showed that Baitul Mal Banda Aceh and Rumah Zakat Aceh had carried out accountability. This can be seen from the procedure for receiving and distributing zakat as well as the existence of financial reports that are routinely made by the management of Baitul Mal Banda Aceh and Rumah Zakat Aceh.